Establishing evidence for the validity for a measure of idealization of adolescent pregnancy and parenthood - Stroupe, Laurie Pendleton (2014)
In the last several years, the long-held opinion that adolescent pregnancy was generallyaccidental has been challenged by findings that a large number of teens may want to becomepregnant or may be ambivalent about becoming pregnant. Research further indicates thatpregnancy ambivalence and pregnancy desire have similar outcomes in terms of pregnancy andparenting at a young age.One line of research posits that overly positive opinions about adolescent pregnancy andadolescent parenting may explain at least part of the pregnancy desire and ambivalence amongadolescents. To that end, Condon, Donovan, and Corkindale (2000) developed and validated thePregnancy and Parenthood Scale (PPS) in Australia for a population of high school students.The current study finds that for a population of public university students in theSoutheastern United States, the PPS shows moderately strong internal consistency and moderateevidence of validity. Additionally, mean responses to some scale items vary by sex, religiousaffiliation, and age.